CHARACTERISING A NOVEL ANTIBODY FOR FULL-LENGTH (ACTIVE) STROMAL DERIVED FACTOR-1α (1–67). (21st November 2014) - Bromage, DI; Yellon, DM; Davidson, SM
Abstract : Rationale for study: Stromal derived factor-1α (SDF-1α) is a chemokine that has been implicated in both acute cardioprotection from ischaemia-reperfusion injury, and chronic cardioprotection by regulating stem cell migration to sites of ischaemic myocardial injury. SDF-1α has a relatively short half-life due to cleavage by dipeptidyl peptidase-4 (DPP-4) into inactive SDF-1α (3–67). However, no convenient method exists to specifically quantify active SDF-1α (1–67) in plasma, as all known antibodies recognize both the intact and cleaved forms. We describe for the first time the characterisation of a novel recombinant antibody for use in an ELISA assay for SDF-1α (1–67). Methodology: A custom antibody against the N-terminus, which is specific to the active form of SDF-1α (1–67), was identified by screening the Human Combinatorial Antibody Library (HuCAL) using a phage-display method (AbD Serotec). After further screening, the best of eight candidate antibodies was chosen and optimised as the capture antibody in a sandwich ELISA. The newly developed ELISA was used to quantify the levels of active SDF-1α (1–67) in various samples. Results: The new ELISA is both sensitive and specific for active SDF-1α (1–67). We report initial results quantifying the levels of active SDF-1α relative to cleaved, inactive SDF-1α in human and rat plasma after preconditioning and other conditions. Conclusions: We describe the development of a specific antibody for active SDF-1α (1–67) and its application in ELISA. This will increase our understanding of the kinetics and enzymatic processing of SDF-1α in acute cardioprotection and stem cell therapy.